Perancangan Aplikasi Child Health Record Berbasis Android - Sofia Latifah Fahmi (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
According to the results of the Indonesia Nutrition Status Study (SSGI) in 2021, as many as 20.8% Baduta and 24.4% Toddlers were stunted/short. In addition to fulfilling nutrition for children, the immunization sector also shows the same thing. During the last 2 years from 2020-2021 the coverage of complete basic immunization for infants has fallen drastically. Researchers developed this application using the SDLC Waterfall model. The waterfall method has the advantage that when all systems can be fully and correctly defined at the beginning of the project, software engineering can run well without any problems. The data collection technique used was secondary data that had been previously collected by other parties using the internet, library research, and books related to research. The Child Health Record application is expected to be an application that can help parents control their children's health from an early age. The immunization feature in the application is expected to increase complete basic immunization coverage for children, increase parental awareness in fulfilling child nutrition, increase parental awareness of children's nutritional status and explore information related to knowledge about children's health. The use of the Child Health Record application can be used since children are 0 years old so that the monitoring process runs optimally. Application development can be developed into a personal health record that can be used as an adult or a family health record.